INTEGRASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN: STUDI TENTANG PERAN GURU DI MADRASAH IBTIDAIYAH ALKHAIRAAT MANADO - Merdi Fratomo Mamonto; Wahyu Wijayati; Rahmawaty Alkatiri; Rahmathias Jusuf (JITU Jurnal Ilmiah Tarbiyah Umat, 2026)
This study aims to analyze the role of teachers in integrating character values into the learning process at Madrasah Ibtidaiyah (MI) Alkhairaat Manado and to examine the influence of a heterogeneous social environment on the implementation of character education. This research employed a descriptive qualitative approach involving the principal, classroom teachers, students, and parents as informants selected through purposive sampling. Data were collected through interviews, observations, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that character values were integrated into the stages of lesson planning, implementation, and assessment. During the planning stage, character values were incorporated into learning objectives, learning activities, and instructional documents. In the implementation stage, teachers fostered character values through habituation, role modeling, rule enforcement, and students’ active participation in learning activities. Character assessment was conducted continuously through observation, attitude journals, questionnaires, and self-assessment. The character values developed included religiosity, honesty, discipline, responsibility, tolerance, mutual respect, religious moderation, social awareness, cooperation, and peaceful living. The implementation of character education was supported by madrasah policies, school culture, and parental involvement. The novelty of this study lies in its focus on character education in an Islamic elementary school situated within a multicultural community. The findings indicate that social and religious diversity serves as a supporting factor in strengthening the values of religiosity, tolerance, religious moderation, cooperation, and peaceful coexistence. Character education at MI Alkhairaat Manado contributes to the development of students who are religious, possess noble character, and are capable of living harmoniously in a diverse society.